Understanding the Biomechanical Properties of Skull Base Tissues Is Essential for the Future of Virtual Reality Endoscopic Sinus and Skull Base Surgery Simulators - Favier, Valentin; Gallet, Patrice; Subsol, Gérard; Captier, Guillaume (Clinical and experimental otorhinolaryngology, 2019)
KCI Citation Count: 0